Performance and feasibility study of a new hybrid solar water heater integrated a small water turbine. Issue 3 (17th January 2022) - Habchi, Abderrahim; Hartiti, Bouchaib; Labrim, Hicham; Fadili, Salah; Ertugrul, Mehmet; Faddouli, Ali; El Hajjam, Nablous; Thevenin, Philippe; Ntsoenzok, Esidor
Abstract: The production of thermal energy by solar water heater (SWH) systems is an idea, which has been analyzed and applied for many years. This paper presents a numerical simulation of a new hybrid SWH, in which two tubular thermoelectric generators (TTEGs) and a small water turbine are used to generate more additional electrical energy. The small water turbine is installed between the outlet of the four absorber tubes and the inlet of the water tank in order to generate more electrical energy from the cold‐water motion. Furthermore, the use of a temperature adjustment concept and an optical concentrator shows many significant improvements on the thermal and electrical performance of the new system. Our main results shows that the overall maximum electrical power of two TTEGs was approximately 348.073 W, corresponding to 2.72% of their overall maximum electrical efficiency. Also, the maximum thermal efficiency of the new system reached to 86.09% with an overall hot water quantity of 1548.57 L/d. The electrical energy produced by the small water turbine is about 89.467 W for a cold‐water flow rate of 3 kg/s. Abstract :